The complete plastid genome and phylogenetic analysis of Gracilaria spinulosa - Tao Liu; Xianming Tang; Xuli Jia; Xiangyu Wu; Min Huang; Jun Zeng; Weizhou Chen (Mitochondrial DNA. Part B. Resources, 2019)
Gracilaria spinulosa is an economical species of marine red algae. The length of its plastid genome sequence is 179,082 bp; a total of 236 genes were determined, including 203 protein-encoding genes, 3 rRNA genes, 29 tRNA genes, 1 ribonuclease gene, and 1 intron inserted into the trnM gene. The gene content and structure of Gracilariaceae species were relatively well conserved. Phylogenetic analysis showed that G. spinulosa had a closer relationship with Gracilaria salicornia in Gracilaria. The complete plastid genome sequence provided will help the understanding of Gracilaria evolution.